Shear‐Wave Velocity Reveals Heterogeneous Geometry of the Main Himalayan Thrust System and Deep Structure Beneath the Nepal Himalayas. (2nd June 2022) - Zhao, Lingfeng; Li, Lun; Liao, Jie; Dong, Shixian; Liang, Yanling; Gao, Rui
Abstract: The Himalayas is currently rising due to the collision of the Indian and Asian plates and hosts frequent earthquakes, some of which are devastating, such as the 2015 Mw 7.8 Gorkha earthquake. Despite the importance of deep dynamic processes to understand the uplift of the Himalayas and the occurrence of large earthquakes, it remains limitedly constrained due to the lack of a detailed three‐dimensional subsurface image under this region. Here, we construct new models of shear‐wave velocity and radial anisotropy down to the 150 km depth from Rayleigh‐ and Love‐wave tomography in the Nepal Himalayas. We find that the 2015 Gorkha earthquake and its main aftershock occurred in a velocity contrast that is presumably interpreted as Main Himalayan Thrust (MHT). A duplex structure, imaged as relatively high velocities, is inferred to exist above MHT under the Lesser Himalayas. This duplex shows heterogeneous features along the strike of the Himalayas that may control the rupture behavior during the occurrence of a large earthquake. Additionally, a low‐velocity anomaly is observed at depths from Moho to 100 km under the Lhasa Terrane and north of the Himalayan Terrane between 85° and 88°E. We interpret this low‐velocity anomaly to be likely caused by mantle upwelling resulting from either possible Indian slab tearing, or northward subduction of the Indian plate. If this is the case, the north‐south trending rifts that situate within the dispersal of the low‐velocity anomaly are probably associated with the mantle upwelling. This study provides a new independent constraint on the geometry of the MHT system and deep dynamic processes occurring in the Nepal Himalaya. Plain Language Summary: The 2015 Mw 7.8 Gorkha (Nepal) earthquake caused great damages to property and lives. It is widely suggested that the motion of a megathrust (i.e, the Main Himalayan Thrust (MHT) is responsible for the large earthquake. In order to understand the geometry of this thrust system and associated deep dynamics, in this study we constructed a three‐dimensional subsurface image of the Nepal Himalayas using surface wave that travels at the surface of the Earth. Our seismic image, together with previous studies of coseismic slip distribution, reveals that rupture behavior of the 2015 Gorkha earthquake and its main aftershock is controlled by the heterogeneous duplex structure (i.e., a system of imbricate thrust faults) of the megathrust. Additionally, we offer seismic velocity evidence for the occurrence of asthenospheric upwelling beneath the north of the Himalayan Terrane between 85° and 88°E that is likely linked with the variable MHT geometry along the strike of the Himalayas and surface exposed north‐south trending rifts. This study provides a new independent constraint on the geometry of the MHT system and deep dynamic processes occurring in the Nepal Himalayas. Key Points: New lithospheric‐scale shear‐wave velocity and radial anisotropy models are constructed using surface‐wave tomography A duplex structure of Main Himalayan Thrust is imaged as relatively high velocities under the Lesser Himalayas, controlling earthquake rupture propagation Mantle upwelling is inferred to occur beneath north of the Himalayan Terrane between 85° and 88°E